Ligustrazine Exerts Cardioprotection in Animal Models of Myocardial Ischemia/Reperfusion Injury: Preclinical Evidence and Possible Mechanisms - Zheng, Qun; Huang, Yue-yue; Zhu, Peng-chong; Tong, Qiang; Bao, Xiao-yi; Zhang, Qi-hao; Zheng, Guo-qing; Wang, Yan (Frontiers in Pharmacology, 2018)
Ligustrazine (Lig) is one of the main effective components of Ligusticum Chuanxiong Hort, which possesses a variety of biological activities in the cardiovascular system. Here, we conducted a preclinical systematic review to investigate the efficacy of Lig for animal models of myocardial ischemia/reperfusion injury and its possible mechanisms. Twenty-five studies involving 556 animals were identified by searching 6 databases from inception to August 2017. The methodological quality was assessed by using Collaborative Approach to Meta-Analysis and Review of Animal Data from Experimental Studies (CAMARADES) 10-item checklist. All the data were analyzed using Rev-Man 5.3 software. As a result, the score of study quality ranged from 2 to 6 points. Meta-analyses showed Lig can significantly decrease the myocardial infarct size, cardiac enzymes and troponin compared with control (P< 0.01). The possible mechanisms of Lig for myocardial infarction are antioxidant,anti-inflammatory, anti-apoptosis activities and improving coronarybloodflow and myocardial metabolism. In conclusion, the findings indicated thatLig exerts cardioprotection through multiple signaling pathways in myocardial ischemia/reperfusion injury.